Use of genomic and phenotypic selection in lines for prediction of testcrosses in maize I: grain yield and its components - Môro, Gustavo Vitti [UNESP]; Santos, Mateus Figueiredo; de Souza Júnior, Cláudio Lopes (Springer Nature, 2017)
Grain yield (GY) is a direct function of its components and these traits to being less complex and highly correlated with yield. The objectives of this study were to map Quantitative Trait Loci (QTL) for GY and its components in maize lines and GY in their testcrosses, to verify its congruence and the possibility to select testcrosses from the predict means of the lines by using markers information. Two hundred and fifty-six S1 lines derived from the cross L-08-05F × L-14-04B of tropical germplasm and the testcrosses of these lines with two testers were evaluated in six environments. The traits analysed in the lines were GY, prolificacy, ear height and diameter, number of rows per ear and kernels per row, kernel depth, grain weight, and GY in the testcrosses. QTL were mapped in the lines and in testcrosses and the predicted means of the lines were computed based on QTL effects and in all markers of the genome. Few QTL detected for GY and its components in the lines were coincident with the QTL for yield in testcrosses. The correlations between the predicted means of the lines and the phenotypic means of the testcrosses were not significant or low for most of the components. The coincidence of the selected lines and testcrosses was very low for all traits and the results were similar for both testcrosses and intensity. It is not possible to select testcrosses by using GY or its components information from the lines, even with the aid of molecular markers.
Keywords: Correlation; Endogamy; Hybridization; Indirect selection; Marker assisted selection; Yield